The Influence of Internal and External Factors of the Company on Dividend Policy and Firm Value (Study on LQ45 Companies in Indonesia Stock Exchange 2015-2017) - winasari, ayu diky; Handini, Sri (Ekspektra : Jurnal Bisnis dan Manajemen, 2020)
Changes in the method of weighting LQ45 shares on the IDX cause investment managers to tend to release issuers with low free float, even though the company’s fundamentals are in stable condition. This makes dividends not the only market cosideration in buying shares. This research aims to analyze the influence of internal and external factors of the company on dividend policy and firm value, and analyze the effect of dividend policy mediating the influence of internal and external factors of the company on firm value from LQ45 Companies listed in Indonesia Stock Exchange 2015-2017 period. Judgement Samplingis used as a sample collection technique. Secondary data is form annual reports and monetary data, were analyzed using Partial Least Square (PLS) with SmartPLS v.3.2.6 software. The result of the research shows that internal factors give a significant positive effect on dividend policy, but external factors did not significantly influence dividend policy. Internal, external and dividend policy give a significant positive effect on firm value, while the company’s internal factors and company external factors do not have an indirect influence on the Firm Value thtough dividend policy.